The role of social influence, charismatic leadership, and social isolation in predicting cult affiliation intentions among Malaysian youth - Ma’rof, Aini Azeqa; Abdullah, Haslinda; H. Hamsan, Hanina (Human Resource Management Academic Research Society, 2024)
This study examines the roles of perceived social influence, charismatic leadership, and social isolation in predicting cult affiliation intentions among Malaysian youth. A quantitative approach was employed with a sample of 413 participants, using Pearson correlation and multiple regression analyses to explore the relationships between the variables. The results indicate that perceived social influence is the strongest predictor of cult affiliation intentions, followed closely by charismatic leadership and social isolation. The findings highlight the importance of peer pressure, influential leadership, and feelings of social isolation in shaping youth susceptibility to cult recruitment. The study suggests that intervention strategies should focus on reducing peer pressure, increasing leadership awareness, and addressing social isolation to mitigate the risk of cult involvement. Policymakers, educators, and community leaders are encouraged to implement programs that promote critical thinking, social engagement, and ethical leadership to reduce the vulnerability of youth to cult recruitment.